Physical, structural and optical properties of willemite-based glass-ceramic doped with erbium oxide - Effendy, Nuraidayani (2017)
Over the past few decades, willemite based glass-ceramics doped with rare earth ions have attracted significant attention on the fabrication and characterization. However, only few of them used the waste glass materials to fabricate the willemite in the form of glass-ceramics. Hence, this study is focused on the production and characterization of willemite glass-ceramics from the SLS glass waste as a source of silicon. A series of ZnO-SLS-Er2O3 glass samples was prepared by the conventional melt-quench technique. Willemite based glass-ceramics were derived from controlled the crystallization process of ZnO-SLS-Er2O3 glass systems. The thermal, chemical and physical properties of glass and glass-ceramics samples were measured by differential thermal (DTA), energy dispersive X-ray fluorescence (EDXRF), average density and linear shrinkage measurement. The differential thermal analysis reveals that the glass transition (Tg) and crystallization temperature (Tc) decrease with the increase of Er2O3 content in the ZnO-SLS glass system. This decrement is due to the ability of Er2O3 in reducing the melt viscosity of the glass network. The elements of ZnO, SiO2, CaO, Na2O, Al2O3, Fe2O3,K2O, NiO and Er2O3were detected in glass samples using EDXRF measurement. The average density and linear shrinkage of glass and glass-ceramics samples are increases with the increment of sintering temperature as well as dopant concentration. Moreover, the structural properties of glass and the formation of willemite crystal phase and morphology varies with sintering temperature was studied by X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM) technique. The XRD measurement showed the formation of stable α-willemite at 700°C sintering temperature.Fourier transform infrared reflection (FTIR) spectroscopy is used to get more information about the functional groups of the studied glass and glass-ceramics samples. The presence of vibrations associated with the SiO4and ZnO4groups would clearly suggest the formation of Zn2SiO4phase. In this study, the optical band gap of glass and glass-ceramics are found to be decrease as the sintering temperature and percentage of dopant increase. Broad green emission at 559 nm under excitation 385 nm that associated to the 4S3/2→ 4I15/2transitions was obtained. These spectra reveal that the luminescence of the samples is increased with the progression of sintering temperature due to the presence of Er3+ions into the willemite crystal. Such luminescence of glass and glass-ceramics are expected to have potential applications in phosphor and optoelectronic devices.